Hydrogeological characterization of the perennial spring “El Pozito” Northeast of the Juárez city mountain, Chihuahua, México - Zuñiga de León, David (2018)
Abstract “El Pozito” spring has been the source of consumption during 50 years by nearby communities of Juárez city, so it can be said that it is perennial. Therefore, two main aims justify the present research. Firstly; Its Physical-Chemical Characterization and Secondly, their hydrological behavior. First, two water samples were obtained, transported and analyzed in the Environmental Laboratory of the UACJ. One of them, was analyzed on April (P18-073) and the other on July of 2018 (P18-145). The results were; a. According to Piper, the two samples were of the Sulphated-Calcic type. b. In relation to dissolved solids both samples, were fresh water, c. Hardness, both were very hard water. d. According to Salinity Index, it is observed that the sample P18-073 belongs to the group C3-S2. Which indicates that it is water with a high risk of salinization and a medium adsorption ratio, on the other hand, the sample P18-145 corresponds to the group C2-S2, showing a high risk of salinization and a medium adsorption ratio? Second, regarded to hydrological behavior, it can be seen that: evapotranspiration were higher than rainfall, so evapotranspiration influenced the discharge of the spring during the period from April to September. The discharge observed and the rainfall and temperatures were recorded (Table 1). Summarizing, the physical and chemical water characterization is associated with the rocks predominately limestone while the hydrological behavior is a consequence of arid climate.